2008
DOI: 10.3892/mmr_00000044
|View full text |Cite
|
Sign up to set email alerts
|

Genotype and phenotype of NAT2 and the occurrence of adverse drug reactions in Mexican individuals to an isoniazid-based prophylactic chemotherapy for tuberculosis

Abstract: Abstract. Isoniazid (INH) is a drug extensively used as a prophylactic and therapeutic agent for human tuberculosis (TB). INH is metabolized by the enzymatic activity of N-acetyltransferase 2 (NAT2). Human NAT2, encoded by a highly polymorphic gene, is involved in the biotransformation of xenobiotics, including drugs and certain chemical carcinogens. Numerous studies have established the correlation between the acetylator phenotype and the NAT2 genotype in several populations; however, little is known regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Biehl et al (6,14) reported that neuropathy developed in 44.0% of patients receiving high-dose isoniazid and in 2.0% of those receiving low doses. In addition to the dose of isoniazid, factors such as patients' nutritional status and the rate of acetylation also increase the risk of neuropathy (15)(16)(17)(18). With the effect of all these factors, an increased blood concentration of isoniazid raises the drug's sideeffect potential (7,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Biehl et al (6,14) reported that neuropathy developed in 44.0% of patients receiving high-dose isoniazid and in 2.0% of those receiving low doses. In addition to the dose of isoniazid, factors such as patients' nutritional status and the rate of acetylation also increase the risk of neuropathy (15)(16)(17)(18). With the effect of all these factors, an increased blood concentration of isoniazid raises the drug's sideeffect potential (7,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…It is surprising that there was no statistically significant difference in the incidence of polyneuropathy between the NAT2 genotype-guided treatment and the standard treatment group (Diaz-Molina et al. 2008 ). This result, and the fact that in some studies no association was found between the genotype or phenotype and the incidence of INH-related adverse reactions (Azuma et al.…”
Section: Discussionmentioning
confidence: 99%